STORY FACE STRATEGY IN READING COMPREHENSION - Nelvia Ibrahim; Rizki Amelia (JISOS: JURNAL ILMU SOSIAL, 2023)
This article suggests how many strategies are used in the teaching and learning process, teachers need to be more creative and innovative in creating new things. This strategy is not yet well known by students and is a new challenge for teachers to display it. if you listen to the steps, it is almost the same as mind mapping, but the difference is that the story face strategy is that students are directed to make pictures based on the stories they read, such as students having to draw two circles that are likened to the right and left eyes, which means displaying the place and character actors in the story, then a triangle is likened to a nose, which means displaying the problems contained in the story, the last is a mouth which is likened to a series of circles representing the main events that lead to the solution. It is hoped that students can see big ideas and details that need support in the form of relational structures and are expected to foster students' interest in reading for the better and supported by the right strategy, and one of them is the use of the Story Face Strategy